Development of Ag-Doped ZnO Thin Films and Thermoluminescence (TLD) Characteristics for Radiation Technology - Hammam Abdurabu Thabit; Norlaili A. Kabir; Abd Khamim Ismail; Shoroog Alraddadi; Abdullah Bafaqeer; Muneer Aziz Saleh (Nanomaterials, 2022)
This work examined the thermoluminescence dosimetry characteristics of Ag-doped ZnO thin films. The hydrothermal method was employed to synthesize Ag-doped ZnO thin films with variant molarity of Ag (0, 0.5, 1.0, 3.0, and 5.0 mol%). The structure, morphology, and optical characteristics were investigated using X-ray diffraction (XRD), scanning electron microscope (SEM), energy-dispersive X-ray spectroscopy (EDX), photoluminescence (PL), and UV–vis spectrophotometers. The thermoluminescence characteristics were examined by exposing the samples to X-ray radiation. It was obtained that the highest TL intensity for Ag-doped ZnO thin films appeared to correspond to 0.5 mol% of Ag, when the films were exposed to X-ray radiation. The results further showed that the glow curve has a single peak at 240–325 °C, with its maximum at 270 °C, which corresponded to the heating rate of 5 °C/s. The results of the annealing procedures showed the best TL response was found at 400 °C and 30 min. The dose–response revealed a good linear up to 4 Gy. The proposed sensitivity was 1.8 times higher than the TLD 100 chips. The thermal fading was recorded at 8% for 1 Gy and 20% for 4 Gy in the first hour. After 45 days of irradiation, the signal loss was recorded at 32% and 40% for the cases of 1 Gy and 4 Gy, respectively. The obtained optical fading results confirmed that all samples’ stored signals were affected by the exposure to sunlight, which decreased up to 70% after 6 h. This new dosimeter exhibits good properties for radiation measurement, given its overgrowth (in terms of the glow curve) within 30 s (similar to the TLD 100 case), simple annealing procedure, and high sensitivity (two times that of the TLD 100).